Fabrication of Co3O4 quantum dot incorporated polyacrylamide ethylene glycol dimethacrylate as a new fiber for solid phase microextraction and trace determination of organophosphorus pesticides in environmental water samples. Issue 30 (8th July 2021) - Aladaghlo, Zolfaghar; Maddah, Bozorgmehr; Fakhari, Ali Reza
Abstract : A solid phase microextraction fiber based on Co3 O4 quantum dot incorporated polyacrylamide-co-ethylene glycol dimethacrylate followed by corona discharge ion mobility spectrometry is shown for trace determination of organophosphorus pesticides in environmental water samples. Abstract : In this paper, a novel solid phase microextraction fiber based on Co3 O4 quantum dot incorporated polyacrylamide- co -ethylene glycol dimethacrylate followed by corona discharge ion mobility spectrometry is presented for the trace determination of organophosphorus pesticides in environmental water samples. Ion mobility spectrometry is a comparatively inexpensive, well-known, robust, and easy to operate analytical instrument. This combination would provide a low-cost, fast, selective, and sensitive quantitative system for detection of organophosphorus pesticides. In order to obtain the best extraction efficiency, the optimization of parameters affecting this method was carried out. After optimization, a solution pH of 7.0, extraction temperature of 60 °C, adsorption temperature of 260 °C, extraction time of 30 min, stirring speed of 750 rpm, and ionic strength of 10% w/w were obtained. Consequently, the presented method showed low limits of detection (0.3–0.6 ng mL −1 ), excellent enrichment factors (PF = 221–263), good linearity ( R 2 > 0.995), and repeatabilities (intra-day: 3.4 to 4.8%) and (inter-day: 4.7 to 6.1%). The reproducibility (RSD% of fiber to fiber) was also investigated by analyzing three as-prepared fibers under the same conditions and was found to be less than 7.6%. Finally, the developed fiber was used for determination of organophosphorus pesticides in the field samples.